A city laid waste : the capture, sack, and destruction of the city of Columbia - Simms, William Gilmore, 1806-1870 (University of South Carolina Press, 2005)
"In the first reissue of these documents since 1865, A City Laid Waste captures the destruction of South Carolina's capital city as Gen. William T. Sherman brought his scorched-earth campaign to a hotbed of secession. William Gilmore Simms, a native South Carolinian and one of the nation's foremost men of letters, was in Columbia and witnessed firsthand the city's capture and destruction. A renowned novelist and poet who was also an experienced journalist and historian, Simms recorded the events of February 1865 in a series of eyewitness accounts published in the first ten issues of the Columbia Phoenix